2017
DOI: 10.1007/s13770-017-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as an Enabling Strategy for Dental Implant and Tissue Regeneration

Abstract: Graphene-based approaches have been influential in the design and manipulation of dental implants and tissue regeneration to overcome the problems associated with traditional titanium-based dental implants, such as their low biological affinity. Here, we describe the current progress of graphene-based platforms, which have contributed to major advances for improving cellular functions in in vitro and in vivo applications of dental implants. We also present opinions on the principal challenges and future prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“…However, in the sintered samples, this correlation did not hold up, since the higher y -carbon level in sample LTS SPS (0.0114) than in the sample LTS + (hBN) 0.01 SPS (0.0076) induced a lower microstrain of 0.12% vs. 0.14%, respectively. The amount of carbon, a biocompatible material, was very low in the sintered samples [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the sintered samples, this correlation did not hold up, since the higher y -carbon level in sample LTS SPS (0.0114) than in the sample LTS + (hBN) 0.01 SPS (0.0076) induced a lower microstrain of 0.12% vs. 0.14%, respectively. The amount of carbon, a biocompatible material, was very low in the sintered samples [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Graphene was used as coating in a titanium implant, enhancing calcium deposition and osteoinduction, and as a stem cell recruitment agent, improving quality and quantity of bone around and in contact with the implant [ 33 ]. Graphene coating also improved the anti-corrosion properties of titanium [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The properties of GO/PMMA make this material advantageous for potential applications as screws or implants fixation. Previous studies [ 25 , 40 ] showed that PMMA filled with GO conforms to physicochemical and mechanical demands of these clinical applications. In this study, we have shown that incorporation of GO into PMMA matrix may provide an additional functionality to the resulting composite material, enhancing its biocompatibility through facilitating osteogenesis.…”
Section: Discussionmentioning
confidence: 99%